2013
DOI: 10.1186/gb-2013-14-6-r68
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective genomic analysis of sorghum adaptation to temperate-zone grain production

Abstract: BackgroundSorghum is a tropical C4 cereal that recently adapted to temperate latitudes and mechanized grain harvest through selection for dwarfism and photoperiod-insensitivity. Quantitative trait loci for these traits have been introgressed from a dwarf temperate donor into hundreds of diverse sorghum landraces to yield the Sorghum Conversion lines. Here, we report the first comprehensive genomic analysis of the molecular changes underlying this adaptation.ResultsWe apply genotyping-by-sequencing to 1,160 Sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
134
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(147 citation statements)
references
References 26 publications
11
134
2
Order By: Relevance
“…In the population studied here, it appears that alleles conditioning early flowering time are in coupling phase linkage with alleles conditioning smaller plant architecture and/or the traits are under positive pleiotropic control. Although the data set to which we have applied a statistical approach aiming to deduce the occurrence of direct unconscious selection may be underpowered, failure to reject the null hypothesis is consistent with tightly linked effects found for Ma1 in sorghum (Thurber et al, 2013) and pleiotropic effects found for Ghd7 in rice (Xue et al, 2008). In Hallauer's Tusón, there was secondary selection for reduced lodging, which could also explain some of the changes in PLH and ERH.…”
Section: Discussionmentioning
confidence: 94%
“…In the population studied here, it appears that alleles conditioning early flowering time are in coupling phase linkage with alleles conditioning smaller plant architecture and/or the traits are under positive pleiotropic control. Although the data set to which we have applied a statistical approach aiming to deduce the occurrence of direct unconscious selection may be underpowered, failure to reject the null hypothesis is consistent with tightly linked effects found for Ma1 in sorghum (Thurber et al, 2013) and pleiotropic effects found for Ghd7 in rice (Xue et al, 2008). In Hallauer's Tusón, there was secondary selection for reduced lodging, which could also explain some of the changes in PLH and ERH.…”
Section: Discussionmentioning
confidence: 94%
“…Linkage disequilibrium between the most significant SNPs for Dw1 and SbFL9.1 is low, suggesting that they represent separate QTL rather than a single QTL with pleiotropic effects on plant height and flowering time (Thurber et al 2013). All joint linkage models for FL-IL that contain families B and C, in which the QTL appears to be segregating, identify the same SNP at 58.842 Mb (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, sorghums bred in the USA prior to 1965 CE, and the photoperiod-insensitive alleles they encode (e.g., prr37 Milo , prr37 Kafir−2 ), were not dispersed outside the United States. Therefore, while the 'conversion' of tropical ecotypes markedly increased the diversity of temperatezone sorghum germplasm, introgression of dwarfism and day neutrality from a single donor inbred cultivar also created a genetic bottleneck at the genomic region spanning the PRR37 locus (Klein et al 2008;Thurber et al 2013). The purpose of the TAES-USDA Sorghum Conversion Program was to convert tropical sorghums to short-stature, early-flowering cultivars and to freely distribute 'converted' sorghums to seed companies and public breeding programs worldwide.…”
Section: Discussionmentioning
confidence: 99%